Osteocalcin and the vasculature - Millar, Sophie (2020)
Osteocalcin (OCN) is an intriguing hormone having established roles throughout the body beyond its origin of the bone extra cellular matrix. Uncarboxylated osteocalcin (ucOCN) is the major form found within the circulation. However, knowledge surrounding the effects of ucOCN within the vasculature is very limited. Therefore, the aim of this thesis was to create a novel portfolio of work examining the effects of ucOCN within the vasculature.